STUDENTS’ DIFFICULTIES IN READING COMPREHENSION AT THE EIGHT GRADE STUDENTS OF SMPN 22 KOTA JAMBI - Aida, Aida (JR-ELT (Journal of Research in English Language Teaching), 2021)
This research aimed to analyze students' difficulties in reading comprehension at SMPN 22 Jambi. This is a qualitative research. The technique of data collection used in this research is observation and interviews. The subjects in this study were students of class VIII G at SMPN 22 Jambi. The results of this study indicate that the difficulties faced by class VIII G students in reading comprehension are four difficulties. Firstly, students have difficulty in understanding complexity of grammar. Secondly, the students has difficulty in knowing certain vocabulary when understanding reading. Thirdly, students have difficulty in using reading strategies, and the last one the students have difficulty in concentrations.